Effects of add-on tipepidine on treatment-resistant depression: an open-label pilot trial. Issue 1 (20th July 2015) - Shirayama, Yukihiko; Suzuki, Masatoshi; Takahashi, Michio; Sato, Koichi; Hashimoto, Kenji
Abstract : Objective: Treatment-resistant depression is a challenging problem in the clinical setting. Tipepidine has been used as a non-narcotic antitussive in Japan since 1959. Methods: We administered tipepidine to 11 patients with treatment-resistant depression. Tipepidine was given for 8 weeks as an augmentation. Results: Tipepidine significantly improved depression scores on the Hamilton Rating Scale for depression. Add-on treatment with tipepidine significantly improved scores on the trail making test and Rey auditory verbal learning test. However, no changes were observed in blood concentrations of stress-related hormones (adrenocorticotropic hormone, cortisol, dehydroepiandrosterone sulphate) with tipepidine augmentation. Conclusion: Tipepidine might be a potential therapeutic drug for treatment-resistant depression.